Boy, were we wrong about dinosaurs! - Kudlinski, Kathleen V.; Schindler, S. D. (New York : Dutton Children's Books, 2005)
Describes how information and ideas about prehistoric dinosaurs are constantly changing as new discoveries are made.
Includes bibliographical references.
Booklist starred
School Library Journal
Wilson's Children
Booklist starred, December 2005
Bulletin (Center for Children's books), January 2006
Keywords: Common fallacies -- Juvenile literature; Dinosaurs -- Juvenile literature; Science -- History -- Juvenile literature; Common fallacies; Dinosaurs; Science -- History; Dinosaurs; Science -- History; Picture books for children